THE ROLE OF PLANT PREPARATIONS IN IMPROVING THE SAFETY AND QUALITY OF MILK IN SUBCLINICAL MASTITIS OF COWS - Larionov Gennady Anatolyevich; Semenov Vladimir Grigoryevich; Baimukanov Dastanbek Asylbekovich; Kosyaev Nikolay Ivanovich; Alekseev Ivan Alekseevich; Nikitin Dmitry Anatolyevich; Karynbayev Amanbay Kambarbekovich (Scientific Journal of Pedagogy and Economics, 2019)
The production of safe and high-quality milk in case of cow disease with mastitis is an urgent task. In the production of milk, it is necessary to strictly observe the technology and the veterinary and sanitary rules for milking, to carry out timely diagnosis and treatment of cows at subclinical mastitis. In the conditions of the Chuvash Republic, an analysis of the causes of lesions in the quarters of the mammary gland was carried out and the main directions for timely diagnosis and prevention of subclinical mastitis of cows were established. The dynamics of affection of udder quarters with mastitis during the lactation period was determined and with a positive effect it was tested the combined use of plant preparations - pihtoin ointment and trauma-gel for the treatment of subclinical mastitis of cows, which ensures the safety and high quality of products. The use of pihtoin ointment in the treatment of cows with subclinical mastitis led to recovery of the udder in 16.7% of the cows. The quantity of mesophilic aerobic and facultative anaerobic microorganisms in milk decreased 1.6 times. The use of the trauma-gel in the treatment of subclinical mastitis in cows led to the recovery of the udder in 63.2% of sick cows. The content of microorganisms in milk declined by 13%. The results of studying the effect of the combined use of pihtoin ointment and trauma-gel preparation on the milk quality of cows showed that with the combined treatment of subclinical mastitis, all 14 sick cows recovered, that was 100%. In the treatment of subclinical mastitis of cows during the lactation period, we recommend the combined use of plant preparations - pihtoin ointment and trauma-gel 2 times a day with an interval of 12 hours for 5 days. The combined use of pihtoin ointment and trauma-gel preparation for the treatment of cows allowed to reduce not only the number of somatic cells and improve the quality of milk, but also the cost of treatment by 3.8 times. Preparations on a plant basis have excluded the damage from milk rejection, which is presented in the treatment with antibiotics.